Optimization of rice byproducts based feed formulation for Indian major carps using linear programming modelling - Priyadarsani, Supriya; Pradhan, Asit Kumar; Debnath, Manish; Jena, Prakash Chandra (ORYZA-An International Journal of Rice, 2026)
The escalating cost of conventional feed ingredients has intensified the demand for alternative, cost-effective, and sustainable inputs in aquaculture nutrition. Rice byproducts, including rice bran, rice polish, broken rice, and de-oiled rice bran, offer considerable potential owing to their abundance, nutrient density, and low market price. This study investigates the optimization of rice-byproduct-based feed formulations for Indian major carps using linear programming (LP) modelling. Rice byproducts, considered waste, were evaluated as cost-effective and nutrient-rich alternatives to conventional aquafeed ingredients. Proximate composition data were incorporated into a linear programming framework to formulate 100 kg of feed using these ingredients, in order to determine optimal combinations that minimize production costs while fulfilling species-specific nutritional requirements for growth and health. Results indicated that for a 100 kg feed formulation, protein contents of 22.17%, 21.32%, and 20.45% could be obtained from the mixture, costing approximately Rs 1693.70, Rs 1704.95, and Rs 1670.95, respectively. This indicates that the formulation will cost less than Rs 20 per kg of feed, without compromising the nutrient content required for the growth of fish at different stages. This will help increase the productivity and profitability of fish farming.